COMPARATIVE ANALYSIS CONCEPT «BREAD» FOR WITNESSES OF THE HOLODOMOR AND THEIR DESCENDANTS - Yevchenko, Iryna; Masliuk, Andrii (PSYCHOLOGICAL JOURNAL, 2020)
The article contains the results of a comparative analysis of the associative series of the word-stimulus «bread» of the Holodomor witnesses and the descendants of the Holodomor witnesses in Ukraine. The scientific approaches to the definition of the concept of traumatic situations, the consequences of trauma are considered. An analysis of modern scientific works devoted to the problems of studying traumatic events suggests that «untreated» trauma adversely affects a person’s personal development and, consequently, the consequences of trauma affect future generations. In order to identify the perceptions of the concept of «bread» by the descendants of the witnesses of the Holodomor, an empirical study was conducted, during which three groups of descendants of the witnesses of the Holodomor were identified: potential children of witnesses of the Holodomor (1st generation), potential grandchildren of witnesses of the Holodomor (2nd generation), potential great-grandchildren of witnesses of the Holodomor (III generation). After analyzing the results, we compared them with the results of the Holodomor witnesses on the word-stimulus «bread», which were obtained by one of the authors during a preliminary psychological study. It is proved that with each generation the traumatic and mythological perception of the concept of «bread» decreases, the third generation of descendants of the witnesses of the famine gives the word «bread» more biological significance as a food product, without idealizing and not attributing extraordinary qualities to the concept of «bread». A promising direction for further research, based on the obtained research material, is a comparative analysis of the concepts of «hunger», «earth», «life», «death» for witnesses of the famine and their descendants.